Propagation‐based x‐ray phase‐contrast tomography of mastectomy samples using synchrotron radiation. Issue 12 (20th October 2019) - Gureyev, T. E.; Nesterets, Ya. I.; Baran, P. M.; Taba, S. T.; Mayo, S. C.; Thompson, D.; Arhatari, B.; Mihocic, A.; Abbey, B.; Lockie, D.; Fox, J.; Kumar, B.; et al.
Abstract : Purpose: Propagation‐based phase‐contrast computed tomography (PB‐CT) is a method for three‐dimensional x‐ray imaging that utilizes refraction, as well as absorption, of x rays in the tissues to increase the signal‐to‐noise ratio (SNR) in the resultant images, in comparison with equivalent conventional absorption‐only x‐ray tomography (CT). Importantly, the higher SNR is achieved without sacrificing spatial resolution or increasing the radiation dose delivered to the imaged tissues. The present work has been carried out in the context of the current development of a breast CT imaging facility at the Australian Synchrotron. Methods: Seven unfixed complete mastectomy samples with and without breast cancer lesions have been imaged using absorption‐only CT and PB‐CT techniques under controlled experimental conditions. The radiation doses delivered to the mastectomy samples during the scans were comparable to those approved for mammographic screening. Physical characteristics of the reconstructed images, such as spatial resolution and SNR, have been measured and compared with the results of the radiological quality assessment of the complete absorption CT and PB‐CT image stacks. Results: Despite the presence of some image artefacts, the PB‐CT images have outperformed comparable absorption CT images collected at the same radiation dose, in terms of both the measured objective image characteristics and the radiological image scores. The outcomes of these experiments are shown to be consistent with predictions of the theory of PB‐CT imaging and previous reported experimental studies of this imaging modality. Conclusions: The results presented in this paper demonstrate that PB‐CT holds a high potential for improving on the quality and diagnostic value of images obtained using existing medical x‐ray technologies, such as mammography and digital breast tomosynthesis (DBT). If implemented at suitable synchrotron imaging facilities, PB‐CT can be used to complement existing imaging modalities, leading to more accurate breast cancer diagnosis.